2000
DOI: 10.1046/j.1365-2036.2000.00788.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: comparison of the pharmacokinetics, acid suppression and efficacy of proton pump inhibitors

Abstract: Proton pump inhibitors have dramatically influenced the management of acid‐peptic disorders in recent years. They all have a broadly similar mechanism of action and are extensively metabolized in the liver via cytochromes P450 2C19 and 3A4. There is some variation in their potential for drug interactions due to differences in enzyme inhibition. Relatively few serious adverse effects have been reported for the proton pump inhibitors. Comparative studies of acid suppression suggest that lansoprazole and pantopra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
229
0
10

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(244 citation statements)
references
References 84 publications
5
229
0
10
Order By: Relevance
“…The only significant difference was occurrence of lesser number of NAB episodes in the ilaprazole group. Acid suppression properties of omeprazole were consistent with other studies [33][34][35] but that of ilaprazole were found to be inferior compared to previous studies. 36,37 This could be explained by probable altered metabolism of ilaprazole in our population compared to other Asian populations, and the higher dose of ilaprazole could have produced better acid suppression than the 10 mg used in our study.…”
Section: Discussionsupporting
confidence: 78%
“…The only significant difference was occurrence of lesser number of NAB episodes in the ilaprazole group. Acid suppression properties of omeprazole were consistent with other studies [33][34][35] but that of ilaprazole were found to be inferior compared to previous studies. 36,37 This could be explained by probable altered metabolism of ilaprazole in our population compared to other Asian populations, and the higher dose of ilaprazole could have produced better acid suppression than the 10 mg used in our study.…”
Section: Discussionsupporting
confidence: 78%
“…Yet, in this study, the suspension formulation seemed to have a higher bioavailability than the MUPS® formulation in seven of 10 patients. Although the therapeutic target AUC for omeprazole is not known, the efficacy of omeprazole correlates with AUC in both adults [13][14][15] and children [16,17]. The suspension formulation therefore seems the better option for the administration of omeprazole through the gastrostomy tube in patients with severe neurodevelopmental problems.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Although there is variation in acid suppression potency between different proton-pump inhibitors, 3 it has been reported that there is no clinically significant difference in H. pylori eradication rates with different proton-pump inhibitor-based regimens. 4 However, a recent meta-analysis showed that a double dose of proton-pump inhibitors when combined with clarithromycin and amoxicillin had an approximately 10% better cure rate than a single dose, 5 confirming the adequacy of acid suppression required for H. pylori eradication therapy.…”
Section: Introductionmentioning
confidence: 99%